Epidemiological and viral genome characteristics of the first human H7N9 influenza infection in Guangdong Province, China - Yang, Zi-Feng; He, Jian-Feng; Li, Xiao-Bo; Guan, Wen-Da; Ke, Chang-Wen; Wu, Shi-Guan; Pan, Si-Hua; Li, Run-Feng; Kang, Min; Wu, Jie; Lin, Jin-Yan; Ding, Guo-Yun; et al. (Journal of Thoracic Disease, 2014)
Background: The first H7N9 human case in south of China was confirmed in Guangdong Province on August 2013, outside of the typical influenza season. For investigating the H7N9 virus source and transmission in the local community, we analyze the epidemiology and genome features of the virus isolated from the first human infection detected in Guangdong Province. Methods: The data including medical records, exposure history and time line of events for the H7N9 patient and close contacts was collected. Variation and genetic signatures of H7N9 virus in Guangdong was analyzed using ClustalW algorithm and comparison with mutations associated with changes in biological characteristics of the virus. Results: The female patient had a history of poultry exposure, and she was transferred from a local primary hospital to an intensive care unit (ICU) upon deterioration. No additional cases were reported. Similar to previous infections with avian influenza A (H7N9) virus, the patient presented with both upper and lower respiratory tract symptoms. Respiratory failure progressed quickly, and the patient recovered 4 weeks after the onset of symptoms. Genome analysis of the virus indicated that the predicted antigen city and internal genes of the virus are similar to previously reported H7N9 viruses. The isolated virus is susceptible to neuraminidase (NA) inhibitors but resistant to adamantine. Although this virus contains some unique mutations that were only detected in avian or environment-origin avian influenza A (H7N9) viruses, it is still quite similar to other human H7N9 isolates. Conclusions: The epidemiological features and genome of the first H7N9 virus in Guangdong Province are similar to other human H7N9 infections. This virus may have existed in the environment and live poultry locally; therefore, it is important to be alert of the risk of H7N9 re-emergence in China, including emergence outside the typical influenza season.